Glyphosate and Microbiota: controversies and truths - Stefania Colantuono; Maria Antonietta Zavarella; Gabriela Leonti; Ilaria Baglivo; Cristiano Caruso; Alfredo Papa (Nutrimentum et Curae)
Glyphosate-based herbicides (GBHs) are currently the most widely used herbicides in the world, and for many years, they have been considered safe for human health due to the assumption that human cells are presumably not directly affected by glyphosate, given the lack of the 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) enzyme. However, the effect of glyphosate on the host-associated microbiota has been recently suggested in several studies. The manuscript is a critical review of the existing literature on the topic, with the aim to focus on the confirmed effects of glyphosate and co-formulants on gut microbiota as the target of potential harmfulness for humans. Moreover, if future evidence will confirm that glyphosate may act as one of the drivers for antibiotic resistance, its global impact on human health will need to be reassessed.